Magister ludens Der Erzähler in Heinrich Wittenweilers "Ring" - Wolf Cross, Christa (UNC Studies in the Germanic Languages and Literatures, 1984)
In this closely argued and admirably lucid study of the late medieval didactic epic "Der Ring", Christa Wolf Cross analyzes the dynamics of the narrator-reader relationship. Wittenweiler's narrator presents himself at times as the omniscient and methodical teller of his tale, an authoritative teacher in command both of his material and his audience, and at other points as a playful master who feigns ignorance, appears to mock his own versifying, and challenges the reader to become vigilant to an extraordinary degree and to recognize that he must judge independently what to accept as Wittenweiler's teachings. Cross's investigation leads her to propound new answers to a number of questions that have long perplexed Wittenweiler scholars. While she has much to say to other specialists, her study addresses itself not to them alone but to a larger audience of students of medieval literature as well.